ABOUT THE BIBLIOPHILIC BOOK IN THE CONTEXT OF THE HISTORY OF LITHUANIAN APPLIED GRAPHICS - BRAZIŪNIENĖ, ALMA (Knygotyra, 2015)
Vilniaus universiteto Knygotyros ir dokumentotyros institutasUniversiteto g. 3, LT-01513 Vilnius, LietuvaEl. paštas: alma.braziuniene@kf.vu.lt